Simulation of Power-Law Fluid Flows in Two-Dimensional Square Cavity Using Multi-Relaxation-Time Lattice Boltzmann Method (Communications in Computational Physics, 2014)
In this paper, the power-law fluid flows in a two-dimensional square cavityare investigated in detail with multi-relaxation-time lattice Boltzmann method (MRT-LBM). The influence of the Reynolds number (Re) and the power-law index (n) on thevortex strength, vortex position and velocity distribution are extensively studied. Inour numerical simulations, Re is varied from 100 to 10000, and n is ranged from 0.25 to1.75, covering both cases of shear-thinning and shear-thickening. Compared with theNewtonian fluid, numerical results show that the flow structure and number of vortexof power-law fluid are not only dependent on the Reynolds number, but also relatedto power-law index.